Perioperative C‐peptide index is associated with the status of diabetes management after pancreatectomy. Issue 10 (28th June 2022) - Shikata, Masataka; Chujo, Daisuke; Enkaku, Asako; Takikawa‐Nishida, Akiko; Honoki, Hisae; Yamada‐Matsukoshi, Shinnosuke; Nakagawa‐Yokoyama, Maki; Kamigishi, Miki; Inagawa, Shinya; Fujisaka, Shiho; Yagi, Kunimasa; Shibuya, Kazuto; et al.
Abstract: Aims/Introduction: This study aimed to identify the clinical factors affecting postoperative residual pancreatic β‐cell function, as assessed by the C‐peptide index (CPI), and to investigate the association between perioperative CPI and the status of diabetes management after pancreatectomy. Materials and Methods: The associations between perioperative CPI and clinical background, including surgical procedures of pancreatectomy, were analyzed in 47 patients who underwent pancreatectomy, and were assessed for pre‐and postoperative CPI. The association between perioperative CPI and glycemic control after pancreatectomy was investigated. Results: The low postoperative CPI group (CPI <0.7) had longer duration of diabetes (17.5 ± 14.5 vs 5.5 ± 11.0 years, P  = 0.004), a higher percentage of sulfonylurea users (41.7 vs 8.7%, P  = 0.003) and a greater number of drug categories used for diabetes treatment (1.9 ± 1.1 vs 0.8 ± 0.8, P  <0.001) than did the high postoperative CPI group. Postoperative CPI was higher (1.4 ± 1.2 vs 0.7 ± 0.6, P  = 0.039) in patients with low glycosylated hemoglobin (<7.0%) at 6 months after pancreatectomy; preoperative (2.0 ± 1.5 vs 0.7 ± 0.5, P  = 0.012) and postoperative CPI (2.5 ± 1.4 vs 1.4 ± 1.1, P  = 0.020) were higher in non‐insulin users than in insulin users at 6 months after surgery. Conclusions: The duration of diabetes and preoperative diabetes treatment were associated with residual pancreatic β‐cell function after pancreatectomy. Furthermore, perioperative β‐cell function as assessed by CPI was associated with diabetes management status after pancreatectomy. Abstract : Perioperative beta cell function as assessed by CPI in patients who underwent pancreatectomy was associated with glycemic control and the requirement of insulin therapy after pancreatectomy.